Breastfeeding impact on kidney health : updated evidence - Hakim RAHMOUNE; Nada BOUTRID; Hala BOUTRID (Nutrition & Santé)
Breastfeeding is extensively acknowledged for its numerous health benefits, particularly during the critical early stages of life. This article synthesizes contemporary evidence regarding the influence of breastfeeding on renal function and health, drawing from a diverse array of international studies. The findings consistently demonstrate that breastfeeding is associated with enhanced renal growth, improved kidney function, and a diminished risk of various renal pathologies. Specifically, breastfed infants exhibit significantly larger renal volumes and elevated glomerular filtration rates, compared to their formula-fed counterparts. Moreover, exclusive breastfeeding correlates with lower incidences of urinary tract infections and nephrotic syndrome. This review reaffirms the critical importance of breastfeeding for both immediate infant health, and its potential to shape renal health throughout life, thereby, supporting the Developmental Origins of Health and Disease (DOHaD) hypothesis, and emphasizing the necessity for ongoing advocacy in this domain.